DIMINUTIVE FORMS IN TITLES OF RUSSIAN FOLKTALES - Jingting, Xu; Ageeva, Juliya; Ling, Wang (Revista Inclusiones, 2019)
The paper presents findings of the linguistic analysis of Russian folktales. The authors of the paper address a little-known aspect of the folktale - the functioning of diminutive forms in the titles of folktales. The object of the study is a collection "Russian Folktales" of Alexander Afanasyev. The subject of the study is titles of folktales. The aim of this paper is to present diminutive forms as one of the important language features in folktales’ titles and to determine their types. This study has been carried out taking into account new trends in linguistic studies which observe the multidimensionality and diversity of linguistic units and allow a more thorough analysis of the world perception by the folktale discourse users. Pursuant to the analysis of linguistic material based on the texts of folktales, the specifics of folktale discourse is determined. The paper analyzes the composition of the titles, classifies various types of suffixes, presents and exemplifies diminutive forms. The most frequent diminutive forms with the suffixes -ечк, -еньк; -очк, -оньк; -ышк, -юшк, - ушк; -ик; -ичк are identified.